A Psychosocial Development of a Young Adult Character in Thirteen Reasons Why Novel - Raden Nur Prasetyo Wibowo, - (2019)
This study analyzes a young adult protagonist character Clay Jensen in Thirteen Reasons Why novel by Jay Asher (2007). The present research investigates the main character's psychosocial development. The novel tells a journey of Clay Jensen who struggles to listen to a series of tapes that reveal reasons why his crush, Hannah Baker, committed suicide in Hannah's voice. The way Clay reflects his emotions and responses to the tapes interest the researcher to analyze his psychosocial development, specifically the psychological and social characteristics. The purposes of this study are to enlist Clay Jensen's psychosocial issues and to discover how he copes with these issues as part of psychosocial development. This textual analysis applied Bucher and Hinton's (2010) developmental characteristics of young adults; the analysis explored Clay Jensen's narrative events that embody the ideas of psychosocial issues and how he deals with the psychosocial issues. It is concluded that Clay Jensen develops psychosocially because he experiences some psychosocial issues such as anxiety and low self-esteem, but he is able to cope with these issues. Clay Jensen is also a round character who develops himself from being selfish to be a more sympathetic person.;---Penelitian ini menyelidiki perkembangan psikososial tokoh remaja Clay Jensen dalam novel Thirteen Reasons Why oleh Jay Asher (2007). Penelitian ini bersifat analisis tekstual. Novel tersebut menceritakan perjalanannya, yang berjuang juga bertahan dengan mendengarkan serangkaian kaset yang mengungkapkan alasan mengapa Hannah Baker, orang yang Clay Jensen suka, bunuh diri dalam sudut pandang Hannah Baker yang disampaikan melalui kaset-kaset tersebut. Cara Clay merefleksikan emosi dan tanggapannya terhadap kaset-kaset tersebut karena ia juga dituduh sebagai penyebab kematiannya membuat peneliti tertarik untuk melihat perkembangan psikososialnya yang mencakup karakteristik psikologis dan sosial. Menemukan masalah-masalah psikososial Clay Jensen dan upayanya mengatasi masalah-masalah tersebut merupakan tujuan dari penelitian ini untuk melihat perkembangan psikososialnya. Penelitian ini juga mengaplikasikan teori perkembangan remaja (young adults) oleh Bucher dan Hinton (2010). Kesimpulannya, Clay Jensen berkembang secara psikososial sebagaimana ia mengalami beberapa masalah psikososial contohnya kecemasan dan rasa akan harga diri yang rendah, namun ia tetap mampu mengatasi masalah-masalah psikososial tersebut. Clay Jensen juga berubah menjadi orang yang lebih simpatik dalam berinteraksi dengan orang lain.